2009
DOI: 10.1016/s1472-9792(09)70007-1
|View full text |Cite
|
Sign up to set email alerts
|

TB Research at UT-Houston – A review of cord factor: new approaches to drugs, vaccines and the pathogenesis of tuberculosis

Abstract: SUMMARY Tuberculosis remains a major threat as drug resistance continues to increase. Pulmonary tuberculosis in adults is responsible for 80% of clinical cases and nearly 100% of transmission of infection. Unfortunately, since we have no animal models of adult type pulmonary tuberculosis, the most important type of disease remains largely out of reach of modern science and many fundamental questions remain unanswered. This paper reviews research dating back to the 1950’s providing compelling evidence that cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Interest in cord factor remains open, mainly due to its adjuvanticity (Khader et al, 2007;Lima et al, 2001;Werninghaus et al, 2009) and its relation to the pathogenesis of tuberculosis (Hunter et al, 2009). Moreover, some aspects of the interaction of cord factor with antigen-presenting cells are being resolved, and recent findings have indicated that the scavenger receptors MARCO (macrophage receptor with collagenous structure) (Bowdish et al, 2009) and Mincle (a C-type lectin receptor) (Ishikawa et al, 2009;Schoenen et al, 2010) are involved in the recognition of this glycolipid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interest in cord factor remains open, mainly due to its adjuvanticity (Khader et al, 2007;Lima et al, 2001;Werninghaus et al, 2009) and its relation to the pathogenesis of tuberculosis (Hunter et al, 2009). Moreover, some aspects of the interaction of cord factor with antigen-presenting cells are being resolved, and recent findings have indicated that the scavenger receptors MARCO (macrophage receptor with collagenous structure) (Bowdish et al, 2009) and Mincle (a C-type lectin receptor) (Ishikawa et al, 2009;Schoenen et al, 2010) are involved in the recognition of this glycolipid.…”
Section: Discussionmentioning
confidence: 99%
“…Cord factor takes part in some specific pathological events of tuberculosis, such as formation of granulomas (the hallmark of primary tuberculosis) and caseation (Hunter et al, 2009), participating in the upregulation of the host lipid metabolism (Kim et al, 2010). It has been demonstrated that cord factor is secreted, together with other lipids, by macrophages infected with Mycobacterium bovis BCG (Rhoades et al, 2003) and that it is the most active lipid from a biological point of view (Geisel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations